Exploring Logical Analysis and Defined Descriptions for Enhancing Expression Readers in ELT - AL Farisi, Muhammad Rafi; Rini, Setia (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The ongoing debate in English Language Teaching (ELT) emphasizes the need for innovative approaches to enhance language acquisition. This study explores the development and implementation of expression readers, a tool designed to improve learners' comprehension and expressive skills through logical analysis and defined descriptions. Logical analysis deconstructs sentences to reveal grammatical and syntactical relationships, while defined descriptions provide clear explanations of linguistic elements. Grounded in a theoretical framework that integrates cognitive engagement and critical thinking, this research examines how expression readers facilitate the structured learning of complex language concepts. The study employs a systematic approach, analysing how these methods enhance students' ability to understand and construct sophisticated sentences. Key findings indicate that expression readers promote deeper linguistic comprehension, improve sentence construction skills, and encourage analytical thinking. The practical implications of this research suggest that integrating expression readers into ELT curricula can enhance language proficiency. To maximize effectiveness, best practices include curriculum adaptation, teacher training, and the development of accessible educational materials. Addressing challenges such as resource availability and learner diversity is crucial to ensuring the successful implementation of this approach in diverse educational settings.